2021
DOI: 10.3389/fimmu.2021.766170
|View full text |Cite
|
Sign up to set email alerts
|

Oral Pathobiont-Induced Changes in Gut Microbiota Aggravate the Pathology of Nonalcoholic Fatty Liver Disease in Mice

Abstract: Background & AimsPeriodontitis increases the risk of nonalcoholic fatty liver disease (NAFLD); however, the underlying mechanisms are unclear. Here, we show that gut dysbiosis induced by oral administration of Porphyromonas gingivalis, a representative periodontopathic bacterium, is involved in the aggravation of NAFLD pathology.MethodsC57BL/6N mice were administered either vehicle, P. gingivalis, or Prevotella intermedia, another periodontopathic bacterium with weaker periodontal pathogenicity, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 92 publications
1
23
1
2
Order By: Relevance
“…Given that the oral mucosa and colonic mucosa are physically connected, oral bacteria could be ingested and translocated to the lower digestive tract, and a possible mechanism of the “mouth-gut axis” has been proposed in the pathogenesis of periodontitis-associated MetS. Notably, a few studies conducted recently demonstrated that oral administration of periodontal pathogens, mainly P. gingivalis , could cause a variety of MetS-related disorders, including increased BMI, insulin resistance, circulatory inflammatory states, and alterations of intestinal permeability and microbiota ( Blasco-Baque et al., 2017 ; Tsuzuno et al., 2021 ; Yamazaki et al., 2021 ). However, little research has focused on the alteration of gut microbiota-derived metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the oral mucosa and colonic mucosa are physically connected, oral bacteria could be ingested and translocated to the lower digestive tract, and a possible mechanism of the “mouth-gut axis” has been proposed in the pathogenesis of periodontitis-associated MetS. Notably, a few studies conducted recently demonstrated that oral administration of periodontal pathogens, mainly P. gingivalis , could cause a variety of MetS-related disorders, including increased BMI, insulin resistance, circulatory inflammatory states, and alterations of intestinal permeability and microbiota ( Blasco-Baque et al., 2017 ; Tsuzuno et al., 2021 ; Yamazaki et al., 2021 ). However, little research has focused on the alteration of gut microbiota-derived metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has proven that transmission and subsequent colonization of the gut by oral bacteria is a common event in healthy subjects [ 142 ]. In periodontitis, swallowed periodontal bacteria can induce gut dysbiosis [ 58 , 143 ] and this is another possible mechanism linking periodontitis and DM [ 138 ].…”
Section: Mechanisms Linking Periodontitis and Dmmentioning
confidence: 99%
“…P. gingivalis-induced gut dysbiosis was paralleled by downregulation of tight junction proteins (TJP-1, occluding) [ 115 , 144 , 145 ], likely leading to enhanced gut permeability and favoring endotoxemia. Of interest, oral administration of P. gingivalis induced changes in the gut microbiota prior to the development of systemic inflammation, suggesting that periodontitis-induced gut dysbiosis may cause endotoxemia, leading then to systemic inflammation and insulin resistance [ 143 ].…”
Section: Mechanisms Linking Periodontitis and Dmmentioning
confidence: 99%
“…From the beginning, periodontitis has contributed to the development of NAFLD owing to systemic inflammation and oxidative stress on the basis of vitro study ( Tomofuji et al, 2007 ). Then, Porphyromonas gingivalis, the main pathogenic bacteria of periodontitis, resulted in the development of NAFLD, above which academic discussion had continued ever since ( Furusho et al, 2013 ; Nagasaki et al, 2021 ; Yamazaki et al, 2021 ). Epidemiological investigation reported that NAFLD incidence was increasing with the combination of periodontitis, which could increase the risk of progression to liver fibrosis as well ( Akinkugbe et al, 2017a ; Akinkugbe et al, 2017b ; Iwasaki et al, 2018 ; Suominen et al, 2019 ; Kuroe et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%